DFID’s approach to value for money in programme and portfolio manageme nt - ICAI (Independent Commission for Aid Impact (ICAI), 2018)
ICAI published this review on DFID’s approach to value for money in Fe bruary 2018, and as value for money is both a process and an outcome a nd cuts across all aspects of DFID’s operations, did not score this re view. We made five recommendations and published a follow-up to this r eview in July 2019. All UK government departments are required to achi eve value for money in their use of public funds. In recent years, DFI D has been working to build value for money considerations further int o its management processes and its relationships with implementers and multilateral partners, establishing itself as a global champion on va lue for money. Review This review was published in February. Though it was not rated, ICAI made five recommendations, and found that the Dep artment for International Development’s approach to value for money wa s helping to make UK aid spending go further, but improvements are sti ll needed. Findings This review found that DFID has strengthened its p rocesses and systems for ensuring it gains maximum value for each poun d spent, has taken swift remedial action to tackle under-performing pr ogrammes, and has become a strong global champion on value for money. The review also found that DFID has been diligent in its efforts to cu t waste, detect fraud, and improve efficiency, and that this work is i mproving the return on the UK investment in aid. However, the review f ound that DFID’s approach was not adequately reporting and capturing r esults and value for money at the country portfolio level, or how prog rammes work together to deliver lasting impact, including reducing fut ure dependency on aid. It also found that weakness in the annual revie w process could undermine DFID’s approach to value for money. It found that targets were frequently revised, and that there could be pressur es for optimistic scoring of programmes. Recommendations Based on this review, we made the following five recommendations to help DFID impro ve its approach to value for money still further: DFID country offices should articulate cross-cutting value for money objectives at the cou ntry portfolio level, and should report periodically on progress at th at level. Drawing on its experience with introducing adaptive programm ing, DFID should encourage programmes to experiment with different way s of delivering results more cost-effectively, particularly for more c omplex programming. DFID should ensure that principles of development effectiveness – such as ensuring partner country leadership, building national capacity and empowering beneficiaries – are more explicit in its value for money approach. Programmes should reflect these principl es in their value for money frameworks, and where appropriate incorpor ate qualitative indicators of progress at that level. DFID should be m ore explicit about the assumptions underlying the economic case in its business cases, and ensure that these are taken into account in progr amme monitoring. Delivery plans should specify points in the programme cycle when the economic case should be fully reassessed. Senior respo nsible owners should also determine whether a reassessment is needed f ollowing material changes in the programme, results targets or context . Annual review scores should include an assessment of whether program mes are likely to achieve their intended outcomes in a cost-effective way. DFID should consider introducing further quality assurance into t he setting and adjustment of logframe targets.